Lung Function Impairment and Workplace Control Measures among Marble Stone Carvers in Sa-Kyin Village, Madayar Township, Myanmar - Htun, Zaw Z; Win, Yi Y; Myat, Aung M; Naing, Soe M (International Journal of Occupational Safety and Health, 2021)
Introduction: Marble rocks, composed of dust containing calcium carbonate and silica particles, predispose to a higher prevalence of occupational lung diseases. This study aimed to assess workplace control measures and lung function impairment among marble stone carvers. Methods: A cross-sectional descriptive study was conducted among 120 marble stone carvers in Sa-Kyin Village, Madayar Township in May 2019. Information about existing control measures in the workplace was assessed using a pre-tested structured questionnaire and participants’ lung function using spirometry. Respirable dust measurements in twelve randomly selected workers were performed by personal air sampling pumps. Results: It was found that 9.2% of marble stone carvers used disposable or cloth masks throughout the working time, but no one was found using appropriate devices like respirators. No one reported about regular medical checkup and provision of health education at the workplaces. Spirometry testing showed 55.8% had lung function impairment. Concentrations of respirable dust ranged from 7.19 to 10.13 mg/m3, significantly higher than the recommended Threshold Limit Value (3 mg/m3). In multivariable logistic regression analysis, development of lung function impairment was associated with age [adjusted Odds Ratio (aOR) = 2.84; 95% CI = 1.02,7.91] and use of face mask (aOR = 0.11; 95% CI = 0.01,0.91). Conclusion: The working environment was found dusty, and a significant proportion of workers had lung function impairment. It is essential to adopt proper dust control measures in stone carving workplaces. Preventive measures like medical surveillance and health education program are vital to reduce the burdens from occupational lung diseases.